2017
DOI: 10.12706/itea.2017.017
|View full text |Cite
|
Sign up to set email alerts
|

La relevancia de las marcas de carne de vacuno para los consumidores. Un análisis interregional

Abstract: A pesar de que la utilización de la marca permite ayudar a diferenciar el producto y a conseguir un mayor grado de lealtad entre los consumidores, la carne de vacuno se vende habitualmente sin marca. Este trabajo investiga el nivel de conocimiento y de compra de la carne de vacuno con distintos tipos de marca y su relación con la calidad percibida y las características de los consumidores. Conocer el papel que ocupa la marca en la mente del consumidor y en la decisión de compra puede ser especialmente relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…According to the literature, different shades of red colour may trigger beef freshness perception in a distinct manner (Font-i-Furnols and Guerrero, 2014). In this sense, our result concords with Resano and Sanjuán (2017), who also showed that consumers attached a medium relevance to red colour among a total of 19 quality cues, in particular to a redder one. These authors also reported that consumers assigned a similar importance to the breed and to the slaughter age.…”
Section: Main Beef Attributes Influencing Consumers' Purchase: Consum...supporting
confidence: 82%
See 2 more Smart Citations
“…According to the literature, different shades of red colour may trigger beef freshness perception in a distinct manner (Font-i-Furnols and Guerrero, 2014). In this sense, our result concords with Resano and Sanjuán (2017), who also showed that consumers attached a medium relevance to red colour among a total of 19 quality cues, in particular to a redder one. These authors also reported that consumers assigned a similar importance to the breed and to the slaughter age.…”
Section: Main Beef Attributes Influencing Consumers' Purchase: Consum...supporting
confidence: 82%
“…Results suggest that attributes related with the beef purchasing establishment (which in our case was mainly referred to the butcher's) were very relevant. This result is at least partially supported; first, by the fact that around two thirds of the consumers who participated in the survey regularly purchase beef at the butcher's, and they stated that they trusted on the advice provided by the butcher; second, by the findings obtained by Resano and Sanjuán (2017), who also found that consumers conferred a high importance to these attributes. However, in our study, the experts expected that establishment attributes were even more important for consumers.…”
Section: Main Beef Attributes Influencing Consumers' Purchase: Consum...mentioning
confidence: 69%
See 1 more Smart Citation